2021
DOI: 10.3935/ljsr.v28i2.411
|View full text |Cite
|
Sign up to set email alerts
|

»Zašto djeca nisu oduzeta na vrijeme? «: Analiza medijskih izvještaja o socijalnim radnicima povodom medijski eksponiranih slučajeva zlostavljanja djeteta

Abstract: During the last several years, the Croatian public has been shaken by tragic violent events involving children within the family. In 2017 a mother killed her threeyear-old son, and in 2019 a father attempted to murder his four minor children. When such things occur, the media and the public try to determine why they were not prevented and who is responsible for their prevention, and the ones who are most frequently considered as responsible are social workers. The aim of this research is to analyse discursive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
3
0
2
Order By: Relevance
“…With the state no longer interested in the collective protection of workers' (especially women's) rights and its prioritisation of austerity policies, the problem of domestic violence is positioned as an individual responsibility. At the same time, the burden of preventing domestic violence is placed solely on the social welfare sector by the media on the occasion of tragic incidents involving either women or children (Rajter, 2015;Stanić, 2021).…”
Section: Social Change and The Position Of Social Workersmentioning
confidence: 99%
See 2 more Smart Citations
“…With the state no longer interested in the collective protection of workers' (especially women's) rights and its prioritisation of austerity policies, the problem of domestic violence is positioned as an individual responsibility. At the same time, the burden of preventing domestic violence is placed solely on the social welfare sector by the media on the occasion of tragic incidents involving either women or children (Rajter, 2015;Stanić, 2021).…”
Section: Social Change and The Position Of Social Workersmentioning
confidence: 99%
“…However, a more recent analysis of media articles on social workers regarding media-exposed cases of child abuse has shown that the most common narrative is that of "inappropriate behaviour of social workers" (Stanić, 2021). In this narrative, the media and the public criticise social workers for not providing adequate child protection and consider them insufficiently professional.…”
Section: Social Workers Are More and More Suffering From Depression A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Navedeno je dovelo do smanjenja smještajnih kapaciteta u ustanovama, no nije dovelo do očekivanog porasta broja udomiteljskih obitelji unatoč donošenju novog Zakona o udomiteljstvu (kojim je među ostalim omogućeno bavljenje udomiteljstvom kao zanimanjem). Nadalje, u nekoliko posljednjih godina svjedočili smo nekolicini tragičnih slučajeva ubojstava ili teškog ozljeđivanja djece od strane roditelja, što je dovelo do povećanja broja prijava centrima za socijalnu skrb, ali i povećanja broja izdvajanja djece iz obitelji (Stanić, 2021.). Stanić (2021.)…”
Section: čImbenici Koji Utječu Na Proces Uparivanjaunclassified
“…Informativna i edukativna uloga medija na ovom planu čini se da često nije dovoljno zastupljena i da preovladava senzacionalistička potraga za pričama koje ne nude moguća rešenja, već pozivaju sistem na proglašavanje krivca, te na kažnjavanje. Takva atmosfera dalje vodi većem oprezu onih koji obavljaju ovu profesiju i sveukupnoj rigidnosti sistema (Stanić, 2021). Rezultati ove studije pokazuju najveći stepen slaganja studenata i studentkinja socijalne politike i socijalnog rada sa tvrdnjom da je slika koju mediji stvaraju o socijalnim radnicima/cama negativna.…”
Section: Diskusija Rezultataunclassified